2014
DOI: 10.2174/1874285801408010130
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility of Campylobacter spp. in Oklahoma Conventional and Organic Retail Poultry

Abstract: Campylobacter is one of the most important foodborne pathogens that cause bacterial gastroenteritis.This study was conducted to investigate the prevalence and antimicrobial resistance of Campylobacter in conventional and organic retail poultry samples purchased from grocery stores in Tulsa, Oklahoma.One hundred and fifty six chilled retail chicken samples (85 conventional and 71 organic) and 65 chilled retail conventional turkey samples were collected in this study. The prevalence of Campylobacter in the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 37 publications
5
50
2
Order By: Relevance
“…In the present study, the high detection rate of Campylobacter was observed in isolates from beef carcasses, and this result also corroborates the reports of Kashoma et al [65] and Premarathne et al [66]. The high rates of Campylobacter detection in turkey samples observed in this study also support those reported by Noormohamed and Fakhr [67] in Oklahoma, USA (17%), and Szosland-Fałtyn et al in Poland (47.37%) [68]. The 240 isolates identified belonging to the genus Campylobacter were then characterised into four species, of which 53 (22.08%) were identified as C. coli, 40 (16.66%) as C. jejuni, and 9 (3.73%) as C. fetus, whereas C. lari was not detected.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the high detection rate of Campylobacter was observed in isolates from beef carcasses, and this result also corroborates the reports of Kashoma et al [65] and Premarathne et al [66]. The high rates of Campylobacter detection in turkey samples observed in this study also support those reported by Noormohamed and Fakhr [67] in Oklahoma, USA (17%), and Szosland-Fałtyn et al in Poland (47.37%) [68]. The 240 isolates identified belonging to the genus Campylobacter were then characterised into four species, of which 53 (22.08%) were identified as C. coli, 40 (16.66%) as C. jejuni, and 9 (3.73%) as C. fetus, whereas C. lari was not detected.…”
Section: Discussionsupporting
confidence: 93%
“…All the tested strains were resistant to at least one antibiotic (100%), and 96.9% of the isolated strains were multiresistant (resistance to at least two antibiotics). Our results are comparable to those reported by other authors [ 36 , 41 ]. Resistance to CIP and/or E was found in most of the isolates that were multidrug-resistant.…”
Section: Discussionsupporting
confidence: 92%
“…It is recognized that since the 20 th century, the number of Campylobacter strains isolated from human samples resistant to E and/or CIP is increasing [ 35 ]. Similar rates of antibiotic resistance to CIP (73.7%), E (21.1%) [ 36 ], chloramphenicol (0.0%), and GM (0.0%) [ 37 ] were reported in USA and Germany. Higher resistance rates than our results were also registered in the USA; 84.2% was recorded to AM, 10.5% to chloramphenicol, and 5.3% to GM [ 36 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Initial work demonstrated that the cecum of turkeys harbored the greatest number of C. jejuni, which could be recovered for several weeks after experimental colonization (Wallace et al, 1998). Commercial turkeys, prior to and at slaughter, and retail meat products, have tested positive for C. jejuni or C. coli (Alter et al, 2005;Kashoma et al, 2014;Logue et al, 2003;Noormohamed and Fakhr, 2014;Thorsness et al, 2008;Wallace et al, 1998;Wesley et al, 2005Wesley et al, , 2009Wright et al, 2008).…”
Section: Introductionmentioning
confidence: 99%